Comparison of drug‐eluting and bare metal stents in large coronary arteries: Findings from the NHLBI dynamic registry. Issue 1 (6th January 2014) - Chan, Chi Yuen; Vlachos, Helen; Selzer, Faith; Mulukutla, Suresh R.; Marroquin, Oscar C.; Abbott, Dawn J.; Holper, Elizabeth M.; Williams, David O.
Abstract : Objectives: This study sought to evaluate the safety and effectiveness of drug‐eluting stents (DES) compared to bare‐metal stents (BMS) for patients with large coronary vessels. Background: Randomized trials have demonstrated that DES reduce the risk of target vessel revascularization (TVR) compared to BMS. This benefit is less pronounced as artery diameter increases. Whether DES are superior to BMS for larger coronary arteries in the setting of routine clinical practice is unknown. Methods: We analyzed data from 869 patients undergoing de novo lesion PCI with reference vessel diameter greater than or equal to 3.5 mm in the NHLBI Dynamic Registry according to whether they were treated with DES or BMS. Patients were followed for 3 years for the occurrence of cardiovascular events. Results: At 3‐year follow‐up, rates of TVR at 3 years were similar and low in both groups (4.4% vs. 3.7%, P = 0.62). After adjustment for differences in baseline characteristics, the adjusted hazard ratio for 3‐year MI for DES was 1.85 (95% CI 0.93–3.7, P = 0.08), for TVR at 3 years 1.14 (95% CI 0.52–2.49, P = 0.75) and for mortality 0.89 (95%CI 0.49–1.62, P = 0.71). Conclusions: In our study of the unrestricted use of DES for patients with lesions in larger diameter coronary arteries, first generation DES did not reduce 3‐year risk of TVR. Our findings do not support the preferred use of DES over BMS for patients with lesions located in arteries >3.5 mm. It is unknown whether secondary generation DES can offer better outcome compared to BMS in large coronary vessels. Further study on this issue is warranted. © 2013 Wiley Periodicals, Inc.